Informed Consent with Children: Ethical and Practical Implications - Henkelman, Julie J.; Everall, Robin D. (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper discusses ideas of informed consent as they apply to working with children. In general, counselling has accepted the view that each person has the right to control his/her own life; however, this right has traditionally been reserved for adults. This paper focuses on how counsellors can deal with issues of consent with children. Suggestions are made for improving the consent process with children in everyday practice.